What Drives German Trend Output Growth? A Sectoral View - Robert Lehmann; Lara Zarges (CESifo GmbH, 2024)
In this paper, we outline material and capital linkages across sectors to quantify the role of the German production network in amplifying sectoral dynamics on aggregate trend gross domestic product growth. This allows us to study the impact of sectoral labor input and total factor productivity trend growth variation on the persistent decline in long-run output growth. Our estimation reveals that sector-specific developments have historically accounted for half of this long-term decline. Zooming into the reunification period, we find a pronounced decline of total factor productivity growth in Professional and Business Services together with a fall in labor input growth in the Construction sector to drive the sharp decline of German trend output growth over the 1990s. We further document significant changes regarding the sectors' importance as input suppliers to the economy over the past decades. Our analysis identifies the labor-intensive Construction sector as a major input hub in the production network, its long-run amplification effect exceeding four times its share in value added. Given the impending demographic change, the low potential for automation in this sector may significantly reduce future German trend output growth.
Keywords: C32; E22; E23; O41; 330; trend GDP growth; sectoral multiplier; amplification effects; structural change